ANALISIS POPULASI DAN HABITAT SEBAGAI DASAR PENGELOLAAN RUSA TOTOL (Axis axis) DI TAMAN MONAS JAKARTA (Habitat and Population Analysis as Basic Information/Aspect of Taman Monas Chital Deer Management) - . Hasnawati; Hadi S. Alikodra; Abdul Haris Mustari (Media Konservasi, 2006)
Since the chital deer species (Axis axis) in Taman Monas Jakarta has some functions such as conservation effort of wildlife animal, as education media for societies and for improving the esthetic value of the park there fore guaranty the continuity of these functions and create the ideal management of chital deer in the park are needed. The research has been conducted to observe. The population and its habitat condition as the basis information of an ideal management of chital deer in Taman Monas Jakarta. The interview method, literature study and field observation has an used to get the accurate data about population and habitat condition of chital deer in Taman Monas Jakarta. Productivity of grass in Taman Monas is 78,150 kg/day. If proper use factor of the grasses is 60% and feed intake of a deer is 5 kg/day, this productivity is only enough to supply nine deers, meanwhile there are seventy three deers in Taman Monas, so that the population is overxistence of deer have special function to improve esthetic value of Taman Monas, therefore the amount of population has to save fifty deers the wever additional grass has to be suplemented everyday to fulfill the requirement of feed for deers.Key words : chital deer, population deer, caring capacity, deer management.